Victims and warriors : violence, history, and memory in Amazonia - High, Casey, 1977- (Interpretations of culture in the new millennium., 2015)
Casey High explores how popular imagery of Amazonian violence has become part of the Waorani's social memory in oral histories, folklore performances, and Indigenous political activism. As Amazonian forms of social memory merge with constructions of masculinity and other intercultural processes, the Waorani absorb missionaries, oil development, and logging depredations into their legacy of revenge killings and narratives of victimhood. High shows how these memories of past violence form sites of negotiation and cultural innovation, and thus violence comes to constitute a central part of Amazonian sociality, identity, and memory.